ВПЛИВ ЗАМІСНИКІВ НА ШВИДКІСТЬ РЕАКЦІЇ МЕТА- І ПАРАЗАМІЩЕНИХ БЕНЗОЙНИХ КИСЛОТ З АНІЛІНОМ, ЩО КАТАЛІЗУЄТЬСЯ ПОЛІБУТОКСІТИТАНАТАМИ - Shteynberg, Leon (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2020)
The polybutoxytitanates catalysis of acylation of anilines by meta- and parasubstituted benzoic acid results in substituted benzanilides. The rate constants of this second-order reaction (the first in terms of aniline and substituted benzoic acid; boiling ortho-xylene, 145 °С) correlates well according to the Hammett equation with two straight lines for individual groups of substituents with ρ = 1.76 (electron donors) and 0.12 (electron acceptors). Oxybenzoic and phthalic acids, that do not react with aniline and inhibit the interaction of the latter with benzoic acid, fall out of this dependence. Based on these data, as well as the results of a previous studies of the interaction of substituted anilines with a benzoic acid made under comparable conditions, a mechanism of bifunctional catalysis due to the formation of titanium polybutoxybenzoates in the first minutes of the reaction in situ — the true catalysts of the process, is proposed. The nucleophilic center of the catalyst can be represented by the carbonyl group of a substituted benzoate bound to a titanium atom, forming an H-bond with hydrogen atoms of the amino group of aniline, thus activated to react with a substituted benzoic acid. The titanium atoms of polytitanate (coordination catalysis) and their complexes with the resulting substituted benzanilides (acid catalysis) can act as the electrophilic center of a catalyst that activates the carbonyl group of a substituted benzoic acid to nucleophilic attack by aniline. A titanium atom bound to a substituted benzoate exhibits, depending on the nature of the substituent, various catalytic activity.